Hypoxia Enhances HIF1α Transcription Activity by Upregulating KDM4A and Mediating H3K9me3, Thus Inducing Ferroptosis Resistance in Cervical Cancer Cells - Jing Xiong; Meifang Nie; Chun Fu; Xiaoshan Chai; Yongjing Zhang; Ling He; Shujuan Sun (Stem Cells International)
Objective. Cervical cancer (CC) is a prevalent cancer in women. Hypoxia plays a critical role in CC cell ferroptosis resistance. This study explored the mechanism of hypoxia in CC cell ferroptosis resistance by regulating HIF1α/KDM4A/H3K9me3. Methods. Cultured SiHa and Hela cells were exposed to CoCl2 and treated with Erastin. Cell viability was detected by MTT assay, and concentrations of iron ion, MDA and GSH were determined using corresponding kits. Expressions of KDM4A, HIF1α, TfR1, DMT1, and H3k9me3 were detected by RT-qPCR, Western blot, and ChIP assay. The correlation of KDM4A and HIF1α was analyzed on Oncomine, UALCAN, and Starbase. CC cells were co-transfected with shKDM4A or/and pcDNA3.1-HIF1α. Iron uptake and release were assessed using the isotopic tracer method. The binding relationship between HIF1α and HRE sequence was verified by dual-luciferase assay. Results. Cell viability and GSH were decreased while iron concentration, MDA, KDM4A, and HIF1α levels were increased in hypoxia conditions. The 2-h hypoxia induced ferroptosis resistance. KDM4A and HIF1α were highly-expressed in CC tissues and positively correlated with each other. KDM4A knockdown attenuated cell resistance to Erastin, increased H3K9me3 level in the HIF1α promoter region, and downregulated HIF1α transcription and translation. H3K9me3 level was increased in the HIF1α promoter after hypoxia. HIF1α overexpression abrogated the function of KDM4A knockdown on ferroptosis in hypoxia conditions. Iron uptake/release and TfR1/DMT1 levels were increased after hypoxia. Hypoxia activated HRE sequence in TfR1 and DMT1 promoters. Conclusion. Hypoxia upregulated KDM4A, enhanced HIF1α transcription, and activated HRE sequence in TfR1 and DMT1 promoters via H3K9me3, thus inducing ferroptosis resistance in CC cells.